Masjid Sebagai Pusat Pendidikan melalui Pesantren Husnul Khatimah Menurut Prespektif Psikologi Positif: Masjid as Centre of Education through Pesantren Husnul Khatimah according to Perspective of Positive Psychology - Moch. Firman Taufik Rachman; Budi Handriantro; Bagus Huda Ibrohim (Prodi PAI, Fakultas Tarbiyah, UNIDA GONTORs Tarbiyah, Universitas Darussalam Gontor, 2025)
Various function of Masjid as a centre of education since the begining of islamic age pulled the society to embrace a program and event in it. As the aging population going to touch it’s peak and the needs of carrying the Lansia is inevetible, Pesantren Husnul Khatimah bring a bunch of method and programs that fix the problems. The method of research is Qualitative based on literature and phenomena description. It leads to show that Masjid take a huge part of elderly education. Since the values of positive psychology studies reveal that masjid and it’s program contribute the elderly students (santri) to have a good relations, feelings of meanings, self acceptance, purpose in life etc.